Value conflicts between local government and private sector in stock public-private partnership projects: A case of China. Issue 6 (28th February 2019) - Zhu, Fangwei; Sun, Mouxuan; Wang, Linzhuo; Sun, Xiuxia; Yu, Miao
Abstract : Purpose: The complexity caused by conflicting values of stakeholders is a critical issue influencing the performance and sustainability of stock public–private partnership (SPPP) projects, which is a special type of public–private partnership (PPP) project in China. The purpose of this paper is to focus on value conflicts between local government and private sector, which are two major stakeholders in SPPP projects, and investigate exchange rules to resolve value conflicts. Design/methodology/approach: Using a mixed method approach, 55 semi-structured interviews were conducted for 15 stakeholders involved in a representative SPPP project. Social network analysis was then adopted to outline the value conflict network based on data drawn from focus group discussions. Finally, 24 value conflicts between local government and private sector were analyzed through another 13 semi-structured interviews in an abductive approach. Findings: Results show that value conflicts between local government and private sector are dynamic and intertwined within and across three project phases, based on which six exchange rules, rationality, Altruism, power consistency, competition, group gain and reciprocity, are identified. Two sets of situational factors which potentially influence exchange rules adopted by the two parties are revealed, namely, urgency and professionality for local government and short-term interests and long-term interests for private sector. A summary of paired exchange rules is provided to predict if value conflicts between the two major stakeholders will be resolved or not. Research limitations/implications: Theoretical implications are twofold. First, the results provide a contribution to PPP project management by investigating value conflicts between local government and private sector, which deepen the understanding on the unique characteristics of SPPP projects. Second, the findings contribute to a comprehensive understanding of social exchange theory by suggesting a summary of condition-based and pair-based exchange rules. Originality/value: One strength of the study is in the concentrated analysis of a single case which allows for a deep understanding of value complexity between local government and private sector in SPPP projects from a dynamic and networked perspective. A guideline is provided for both parties when a value conflict is found hard to resolve. Besides, this study is also among the first that addresses value issues in SPPP projects.